Methyl Salicylate Level Increase in Flax after Fusarium oxysporum Infection Is Associated with Phenylpropanoid Pathway Activation - Boba, Aleksandra; Kostyn, Kamil; Kostyn, Anna; Wojtasik, Wioleta; Dziadas, Mariusz; Preisner, Marta; Szopa, Jan; Kulma, Anna (Frontiers in Plant Science, 2017)
Flax (Linum usitatissimum) is a crop plant valued for its oil and fibre. Unfortunately, large losses in cultivation of this plant are caused by fungal infections, with Fusarium oxysporum being one of its most dangerous pathogens. Among the plant’s defence strategies, changes in the expression of genes of the shikimate/phenylpropanoid/benzoate pathway and thus in phenolic contents occur. Among the benzoates, salicylic acid and its methylated form methyl salicylate play an important role in regulating plants’ response to stress conditions. Upon treatment of flax plants with the fungus we found that methyl salicylate content increased (4.8-fold of the control) and the expression profiles of the analysed genes suggest that it is produced most likely from cinnamic acid, through the β-oxidative route. At the same time activation of some genes involved in lignin and flavonoid biosynthesis was observed. We suggest that increased methyl salicylate biosynthesis during flax response to F. oxysporum infection may be associated with phenylpropanoid pathway activation.